againaba Daya Saing Industri Life Sciences di Indonesia - Ernawati Pasaribu; Retno Indrawati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2015)
Indonesia is the South East Asia’s largest economy and has a substantial and increasingly inspirational middle class of over 20 million. Indonesia has become an attractive market due to her strongly growing consumer market, especially the middle income segment. The high number of population also indicates the existing potential pool of labour. Life Sciences (LS) industry is widely recognised as the new wave of knowledge-based economy. This study identifies relative position of Indonesia in terms of foreign direct investment (FDI) in LS industry and competitiveness of the LS industry in Indonesia compared with other countries. Based on LS sector, Indonesia has to compete mainly with Portugal, Turkey, Saudi Arabia and Nigeria, while based on LS activities, Argentina and Bulgaria are the main competitors. It also reveals that FDI inflow to LS industry in Indonesia is influenced mainly by inflation and return on investment.